Environmental perspectives of the producing of biogas-bio humus complexes in Central Asia - Yuliyev O.O; Norov S.N. (Genius Journals, 2023)
The article covers the environmental perspectives of the creation of biogas-biohumus complexes in the arid zones of Central Asia
Keywords: biogas; mesophilic temperature regime; vetan digestion